Estudo da carbonatação de concretos com adição de nanosílica - Pereira, Fernando do Carmo (2019)
The degradation of reinforcing concrete structures reflects in economic and environmental factors. Thus, the desire to minimize it motivates recent research, which aims to add nanomaterials to the cement matrix, seeking to change and improve its properties, among them durability. Nanosilica is a mineral addition with a diameter ranging from 3 to 150 nm, which interacts chemically and physically in the hydration reactions of the cement and in the microstructure of the concrete. Its use still demands knowledge regarding the effect of its incorporation in cementitious composites, such as its influence on the carbonation of the concrete. The penetration of CO2 decreases its alkalinity and generates the disassembling of the armature, which may come running in the presence of oxygen and water, compromising the durability of the structure. In this context, the present work evaluates the accelerated carbonation in concrete with nanosilica, when submitted to the attack of CO2. Traces were formulated with two different water / binder ratios, 0,40 and 0,56. The superplasticizer additive was incorporated only in concretes with water binder ratio equal to 0,40 in order to guarantee the established consistency (230 ± 10 mm). In addition to a reference trait (without mineral addition), cylindrical test specimens (50x100 mm) with different nanosilica contents (1%, 5% and 10%) were molded, as well as a trace with 1% addition of nanosilica together with 10% active silica. The accelerated carbonation tests were performed under two different conditions, a chamber with 15 ± 2% CO2 concentration, relative humidity of 75 ± 5% and temperature of 23 ± 2 °C, and another with a concentration of 3,0 ± 0,5% carbon dioxide, relative humidity 65 ± 5%, and temperature 27 ± 2 °C. In some traits, the pH of the simulated pore solution was also evaluated and microstructural pulp assays performed. The results of the mechanical strength and water absorption tests by capillarity indicate a better performance of the concretes with water/binder ratio equal to 0,40 and the trace with 10% addition of nanosilica showed to be more efficient. In the tests of durability only the specimens with water / binder ratio equal to 0,56 presented carbonation front, independent of the concentration of CO2 to which they were submitted, and there was a greater advance of the attack of CO2 in the trace with addition of 1% of nanosilica and 10% of active silica. The pH evaluation of the simulated pore solution made it possible to observe the clear difference between the values of the carbonate region and the interior of the still uncarbonated test specimen and the microstructural tests indicate a higher amount of calcium hydroxide in the reference trace. Finally, it can be concluded that in larger water/binder ratios, the effect of the porosity on the porosity of the concrete may overlap with the effect of the mineral addition of pore refinement, but the influence of these additions on the mechanical and physical properties, because in the traces with relation water/binder equal to 0,56, in spite of improving them, the addition of nanosílica damages the resistance of the concrete against the attack of CO2, due to the pozzolanic reactions that result in a lower alkaline reserve, and thus, collaborate to further advance the carbonation front.